Designing a C(84) fullerene as a specific voltage-gated sodium channel blocker - Hilder, Tamsyn A (Springer, 2013)
Fullerene derivatives demonstrate considerable potential for numerous biological applications, such as the effective inhibition of HIV protease. Recently, they were identified for their ability to indiscriminately block biological ion channels. A fullerene derivative which specifically blocks a particular ion channel could lead to a new set of drug leads for the treatment of various ion channel-related diseases. Here, we demonstrate their extraordinary potential by designing a fullerene which mimics some of the functions of μ-conotoxin, a peptide derived from cone snail venom which potently binds to the bacterial voltage-gated sodium channel (Na(v)Ab). We show, using molecular dynamics simulations, that the C(84) fullerene with six lysine derivatives uniformly attached to its surface is selective to Na(v)Ab over a voltage-gated potassium channel (Kv1.3). The side chain of one of the lysine residues protrudes into the selectivity filter of the channel, while the methionine residues located just outside of the channel form hydrophobic contacts with the carbon atoms of the fullerene. The modified C(84) fullerene strongly binds to the Na(v)Ab channel with an affinity of 46 nM but binds weakly to Kv1.3 with an affinity of 3 mM. This potent blocker of Na(v)Ab may serve as a structural template from which potent compounds can be designed for the targeting of mammalian Nav channels. There is a genuine need to target mammalian Nav channels as a form of treatment of various diseases which have been linked to their malfunction, such as epilepsy and chronic pain.